The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00345-016-1929-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study comparing the four tract dilation methods of percutaneous nephrolithotomy

Abstract: All the four methods of dilation are equally safe and effective but both OSD and BD are advantageous in terms of lesser fluoroscopy time during dilation. OSD is much cheaper option when compared to BD, and therefore with more experience, it can become the preferable dilation method, especially in the developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 14 publications
1
63
1
3
Order By: Relevance
“…OSD was determined to significantly decrease the transfusion rate, hemorrhage rate and the extent of hemoglobin decrease compared with those of MTD. These results support the results of previous studies (6,(8)(9)(10)(11)(12)(13)(14)(18)(19)(20). In addition, no statistically significant differences were observed between the two groups regarding the stone-free rate.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…OSD was determined to significantly decrease the transfusion rate, hemorrhage rate and the extent of hemoglobin decrease compared with those of MTD. These results support the results of previous studies (6,(8)(9)(10)(11)(12)(13)(14)(18)(19)(20). In addition, no statistically significant differences were observed between the two groups regarding the stone-free rate.…”
Section: Discussionsupporting
confidence: 91%
“…Tract creation and dilation are fundamental steps in percutaneous renal surgery and are required for three traditional types of dilation, including MTD, AD and BD (21)(22)(23). OSD was first introduced by Frattini et al (6); several studies have investigated the safety and effectiveness of OSD compared with those of other methods (7)(8)(9)(10)(11)(12)(13). Numerous RCTs on these methods have been reported and a previous meta-analysis has been published by Cao et al (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude for the dilatation techniques, comparative studies showed that none of the aforementioned dilatation methods were significantly better than another, and the choice depends on the clinical situation, stone condition and surgeon's preference …”
Section: Pcnlmentioning
confidence: 99%
“…63,64 To conclude for the dilatation techniques, comparative studies showed that none of the aforementioned dilatation methods were significantly better than another, and the choice depends on the clinical situation, stone condition and surgeon's preference. 65,66 Size of tract Currently, there are at least two nomenclature for PCNL tract size, which might lead to confusion (Table 2). 67,68 Although the stone clearance rate is good with the standard PCNL, mini-PCNL has been shown to have less blood loss, reduced hospital stay and more tubeless procedures without compromising the stone clearance rate or increasing the infective complications.…”
Section: Dilatation Of Tractmentioning
confidence: 99%